2019
DOI: 10.3389/fendo.2019.00324
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Radiopharmaceutical Evidence for MCHR1 Binding Sites in Murine Brown Adipocytes

Abstract: [ 11 C]SNAP-7941 and its radiofluorinated, fluoro-ethyl derivative [ 18 F]FE@SNAP have been developed as the first positron emission tomography tracers for melanin-concentrating hormone receptor 1 (MCHR1) imaging. Accumulation of these MCHR1 PET-tracers in rat brown adipose tissue (BAT) in vivo provided first indication of MCHR1 expression in rodent BAT. To rule out off-target binding, affinity of both MCHR1 ligands toward adrenergic beta-3 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…[ 18 F]FDG is GLUT-dependently transported into cells mainly via GLUT1 ( Wiebe 2001 ) which is predominantly expressed in C2C12 ( Calderhead et al, 1990 ) and HepG2 cells ( Takanaga et al, 2008 ) and allows to monitor basal glucose uptake. [ 18 F]FDG uptake was investigated at a single time point and by real-time kinetic measurements over 60 min using LigandTracer ® Yellow (Ridgeview Instruments, Sweden) ( Balber et al, 2019 ). Briefly, C2C12 (0.16 × 10 6 ) and HepG2 (1.2 × 10 6 ) cells were seeded into a six well plate and incubated with 4 ml UCB treatment solution for 5 and 24 h followed by 2 h glucose starving in the presence of UCB.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]FDG is GLUT-dependently transported into cells mainly via GLUT1 ( Wiebe 2001 ) which is predominantly expressed in C2C12 ( Calderhead et al, 1990 ) and HepG2 cells ( Takanaga et al, 2008 ) and allows to monitor basal glucose uptake. [ 18 F]FDG uptake was investigated at a single time point and by real-time kinetic measurements over 60 min using LigandTracer ® Yellow (Ridgeview Instruments, Sweden) ( Balber et al, 2019 ). Briefly, C2C12 (0.16 × 10 6 ) and HepG2 (1.2 × 10 6 ) cells were seeded into a six well plate and incubated with 4 ml UCB treatment solution for 5 and 24 h followed by 2 h glucose starving in the presence of UCB.…”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]FDG uptake in BAT as a measure for BAT activity is also enhanced by the ADRB3 agonist CL316,243, as reported by Mirbolooki et al 58 Consequently, one could assume that both ADRB3 agonism and MCHR1 antagonism have the same activating effect on BAT. The mechanism of BAT activation through MCHR1 antagonists has been previously postulated by Ito et al 31 However, since SNAP-7941 also binds to the ADRB3 when administered in a high concentration, 45 we cannot exclude that the observed BAT activation is at least partially attributed to ADRB3 agonism.…”
Section: Mchr1 Protein Is Expressed In Rodent Batmentioning
confidence: 74%
“…The sequence similarity between β-adrenoceptors and MCHR1 already suggests the off-target effects of MCHR1 antagonists. 50 Both MCHR1 antagonists, SNAP-7941 and FE@SNAP, were shown to bind to the ADRB3 only in a micromolar range (SNAP-7941: K i = 14.5 ± 0.3 μM, FE@SNAP: K i = 65.1 ± 2.9 μM), 45 demonstrating a high selectivity against the target protein. As PET-tracers are applied in a pico-to nanomolar range, PET imaging with affinity, and selectivity in a previous study, 40 we chose the carbon-11 tracer to further investigate the in vitro uptake in murine brown adipocytes.…”
Section: Mchr1 Protein Is Expressed In Rodent Batmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Schwindinger et al (2004) reported that the mice which were lacking GNG3 had a significantly reduced weight. Balber et al (2019) reported that MCHR1 expression was increased in BAT, and the use of MCHR1 antagonists in rodents was able to reduce adipogenesis. It is well known that obesity is a risk factor of CAD and the findings of these genes may suggest that they may be indirectly involved in CAD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%